2011
DOI: 10.1590/s1808-86942011000500004
|View full text |Cite
|
Sign up to set email alerts
|

Ortner's syndrome: case series and literature review

Abstract: More than a century ago, Ortner described a case of cardiovocal syndrome wherein he attributed a case of left vocal fold immobility to compression of the recurrent laryngeal nerve by a dilated left atrium in a patient with mitral valve stenosis. Since then, the term Ortner's syndrome has come to encompass any nonmalignant, cardiac, intrathoracic process that results in embarrassment of either recurrent laryngeal nerve-usually by stretching, pulling, or compression; and causes vocal fold paralysis. Not surprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
69
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 17 publications
1
69
0
Order By: Relevance
“…This thoracic course makes the recurrent laryngeal nerve vulnerable to injury and it has been suggested that compression of the nerve between the dilated pulmonary artery and the aorta occurs among almost all patients with cardiovascular disease. 7 In the current case, the left recurrent laryngeal nerve palsy was due to the compression of the nerve between the dilated pulmonary artery and thoracic aorta, in which the dilated pulmonary artery was secondary to pulmonary hypertension. Initially, the suspected cause of the recurrent laryngeal nerve palsy was a mediastinal lymph node; however, this was ruled out by the chest CT scan.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This thoracic course makes the recurrent laryngeal nerve vulnerable to injury and it has been suggested that compression of the nerve between the dilated pulmonary artery and the aorta occurs among almost all patients with cardiovascular disease. 7 In the current case, the left recurrent laryngeal nerve palsy was due to the compression of the nerve between the dilated pulmonary artery and thoracic aorta, in which the dilated pulmonary artery was secondary to pulmonary hypertension. Initially, the suspected cause of the recurrent laryngeal nerve palsy was a mediastinal lymph node; however, this was ruled out by the chest CT scan.…”
Section: Discussionmentioning
confidence: 61%
“…6 Other causes of hoarseness in cardiac disorders include lymphadenitis in the aortic window, pressure from the left bronchus, right ventricular hypertrophy, pulmonary artery atherosclerosis, the anatomical position of the ligamentum arteriosum, a dilated pulmonary artery, mitral regurgitation, atrial myxoma or a left ventricular aneurysm. 7 ethambutol. However, due to patient noncompliance, the treatment was discontinued after two months and was only resumed five months later.…”
Section: Discussionmentioning
confidence: 99%
“…Elimination of compression over the nerve may reverse the hoarseness if the duration is not critically long and nerve is not irreversibly damaged. However, ischemia related nerve damages are not associated with good prognosis [1][2][3][4].…”
mentioning
confidence: 99%
“…Cardiovocal syndrome, or Ortner's syndrome, is an example of a disorder characterized by hoarseness, due to cardiovascular pathology, as described by Nobert Ortner (13,31,38). Cardiovocal syndrome is caused by an impaired ability of the left RLN to transmit impulses to laryngeal musculature because of stretching or impingement on the nerve from diseaseinduced changes in cardiac or great vessel anatomy (31).…”
mentioning
confidence: 99%
“…Cardiovocal syndrome is caused by an impaired ability of the left RLN to transmit impulses to laryngeal musculature because of stretching or impingement on the nerve from diseaseinduced changes in cardiac or great vessel anatomy (31). Hoarseness attributed by Ortner to left RLN damage caused by left atrium dilation in mitral stenosis is controversial.…”
mentioning
confidence: 99%